Moral relativist semantics - Evers, HWA (2007)
Many antirealist views of moral language are highly problematic. I argue that relativist analyses are promising alternatives. I start by looking at the views of Gilbert Harman and present two analyses inspired by his work. I argue that they withstand a large number of objections. These analyses are classical in the following sense: they imply that something is right or wrong relative to the acceptance of certain rules, or relative to certain motivations. But they don't imply that the concept of truth itself is relative. I argue that truth relativism does not provide a viable alternative to classical relativist semantics.